Pengaruh Komposisi Media Tanam dan Dosis Pupuk Nitrogen Terhadap Pertumbuhan Tanaman Bit Merah (Beta vulgaris L.) - Anissa Diah Nuryanti; Widi Wurjani; Rr Djarwatiningsih P.S (Wahana-Bio: Jurnal Biologi dan Pembelajarannya, 2022)
Red beet (Beta vulgaris L.) is a plant with low productivity, so it is necessary to increase productivity by optimally cultivating plants. This study aims to examine the composition of the planting medium and the right dose of nitrogen fertilizer to increase the growth and yield of red beet plants which was carried out from March to June 2022 in Sengkrakan Hamlet, Bedali, Lawang District, Malang Regency, East Java. This study was designed using a factorial randomized block design (RAKF) with the first factor being the composition of the growing media consisting of three levels, namely, soil, soil and compost, soil and cow manure. The second factor is the dose of nitrogen fertilizer which consists of four levels, namely, 50 kg N/ha, 75 kg N/ha, 100 kg N/ha and 125 kg N/ha. The analysis used in this study is analysis of variance followed by the BNJ test at 5% level with the help of computer programs MS. Excel and SPSS. Combination treatment of soil planting media composition and cow manure with a dose of nitrogen fertilizer 50 kg N/ha can increase the height of red beet plants aged 35, 42, 63 and 70 days after planting, increase the number of leaves of red beet plants aged 14 and 28 days after planting and increase dry weight. red beet plant.